Progetto Destination: uno strumento per la tutela del territorio attraverso la conoscenza del rischio associato al trasporto di merci pericolose su strada - Borghetti, Fabio; Gandini, Paolo (GEOmedia, 2014)
The DESTINATION Project, "Monitoring the transport of dangerous goods as a means of protecting the territory” started in 2010 with the aim to quantify and manage the risk related to the transport of dangerous goods by road, considering both anthropic and environmental vulnerabilities. To achieve this goal the GIIS - Global Integrated Information System - was developped to collect territorial data as well as data coming from the monitoring activity of Dangerous Goods Transports. The GIIS processes these data by elaborations and simulations in order to create risk maps.